Tobacco industry manipulation of tobacco excise and tobacco advertising policies in the Czech Republic: an analysis of tobacco industry documents. - Risako Shirane (Public Library of Science (PLoS), 2012)
Background The Czech Republic has one of the poorest tobacco control records in Europe. This paper examines transnational tobacco companies' (TTCs') efforts to influence policy there, paying particular attention to excise policies, as high taxes are one of the most effective means of reducing tobacco consumption, and tax structures are an important aspect of TTC competitiveness. Methods and findings TTC documents dating from 1989 to 2004/5 were retrieved from the Legacy Tobacco Documents Library website, analysed using a socio-historical approach, and triangulated with key informant interviews and secondary data. The documents demonstrate significant industry influence over tobacco control policy. Philip Morris (PM) ignored, overturned, and weakened various attempts to restrict tobacco advertising, promoting voluntary approaches as an alternative to binding legislation. PM and British American Tobacco (BAT) lobbied separately on tobacco tax structures, each seeking to implement the structure that benefitted its own brand portfolio over that of its competitors, and enjoying success in turn. On excise levels, the different companies took a far more collaborative approach, seeking to keep tobacco taxes low and specifically to prevent any large tax increases. Collective lobbying, using a variety of arguments, was successful in delaying the tax increases required via European Union accession. Contrary to industry arguments, data show that cigarettes became more affordable post-accession and that TTCs have taken advantage of low excise duties by raising prices. Interview data suggest that TTCs enjoy high-level political support and continue to actively attempt to influence policy. Conclusion There is clear evidence of past and ongoing TTC influence over tobacco advertising and excise policy. We conclude that this helps explain the country's weak tobacco control record. The findings suggest there is significant scope for tobacco tax increases in the Czech Republic and that large (rather than small, incremental) increases are most effective in reducing smoking.